Perancangan Sistem Deteksi Kelelahan Digital Mahasiswa Berbasis Web dengan Metode RAD - Adi Mulyono (Jurnal Riset Informatika dan Inovasi, 2026)
The increasing integration of digital technology in academic activities has led students to rely heavily on electronic devices for learning purposes. Prolonged use of digital devices may result in digital fatigue, which can affect learning concentration, academic performance, and overall well-being. This study aims to design a web-based information system capable of identifying digital fatigue levels among university students. The Rapid Application Development (RAD) method is applied due to its fast and flexible development approach. The proposed system combines data on device usage duration with questionnaire-based assessments of student fatigue levels. The outcome of this research is a system design that presents digital fatigue information through analytical reports and graphical visualization. This system is expected to support universities in conducting early monitoring of student digital fatigue and promoting healthier digital usage behavior.